Análise da circulação natural monofásica sob movimento de balanço em ambiente marinho - Conceição, Natasha Magalhães (2019)
A marine reactor is affected by the ship motion. In certain situations, vessels may be inclined under small angles or in rolling motion about the longitudinal axis passing through the center of gravity of the vessel’s float area. Therefore, this work investigates the behavior of the coolant in a single-phase natural circulation of a rectangular circuit under small inclination angles and under rolling motion. The circuit presents a horizontal heater and a horizontal cooler. In the inclined case, the geometric size of the circuit varies. All implementations are performed in Wolfram Mathematica 11.3 Student Edition software. Firstly, the natural circulation is analyzed for the steady state, where the circuit is under certain angles of inclination. It results in a transcendental equation for the mass flow rate. As a conclusion, the mass flow decreases as the tilt angle increases. Then, the behavior of the natural circulation is analyzed for different amplitudes of rolling motion and different periods of rolling motion. In this case, the temperature of the fluid varies with space and time. Therefore, the finite difference method is used to perform the semi-discretization of the energy conservation equation in the spatial variable, in order to obtain the temperature distribution along the loop and, then, the mass flow as a function of time is determined. The results of this last case indicate that the mass flow oscillates with the same period of rolling motion. Moreover, for a same value of the period of rolling motion, the amplitude of the mass flow increases with the amplitude of rolling motion. Whereas, for a same value of amplitude of rolling motion, the amplitude of the mass flow decreases when the period of rolling motion increases.